On the interharmonic emission of PV inverters under different operating conditions - Langella, R.; Testa, A.; Djokic, S. Z.; Meyer, J.; Klatt, M. (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
This paper presents the results of experimental evaluation of interharmonics produced by PV inverters (PVInv) for a range of different operating conditions. First, intrinsic interharmonic generation due to Maximum Power Point Tracking (MPPT) control is analyzed. Afterwards, generation of current interharmonics assessment is analyzed adopting the IEC 61000-4-7 sub-group concept and their effects on the supply voltage are evaluated in terms of short-term flicker index, P st . Finally, the paper investigates interharmonic currents produced by PVInvs when harmonics and interharmonics are superimposed to the fundamental supply voltage.